Gender Considerations for Just and Strong Food Systems - Brown, Lynn (2023)
Lynn Brown CGIAR SEMINAR SERIES Food Security Trends and Resilience-Building Priorities Co-organized by IFPRI, the CGIAR, and Germany’s Federal Ministry for Economic Cooperation and Development (BMZ) SEP 1, 2023 - 9:00 TO 10:30AM EDT